Pengaruh Program Orientasi, Budaya Organisasi Terhadap Kinerja Karyawan di PT Pegadaian Belopa - Enjeli Enjeli; Altri Wahida; Samsinar Samsinar (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to investigate the influence of orientation programs, organizational culture on employee performance at PT Pegadaian Belopa. This research was conducted at PT. Belopa Pawnshop is located in Tampumia Radda, Belopa District, Luwu Regency, South Sulawesi. And the research time was carried out for approximately 2 months. This study uses a quantitative research method with an experimental research design with a population of 30 employees. The sample determination technique in this study used a saturated sampling method of 30 respondents, data collected through questionnaires and interviews with respondents. The data analysis techniques used were descriptive statistical analysis, validity and reliability tests, multiple linear regression, T test and F test using the help of IBM 29 SPSS. The results of the study show that the orientation program, organizational culture have a significant influence on employee performance. Employees who take part in the onboarding program, organizational culture have better performance compared to employees who do not participate in the program. This shows that an onboarding, organizational culture program can improve employee job satisfaction by helping them understand the company's goals and mission.